China and the United States: Different economic models but similarly low levels of socioeconomic mobility - Roy van der Weide; Ambar Narayan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The United States and China are the world's largest economies. Together they are responsible for about one-third of the world's economic output. This paper aims to examine whether the two economic giants are also lands of opportunity where resources are allocated in a way that minimizes unrealized human potential. Our analysis shows that despite stark differences in their levels of development, the US and China report remarkably similar levels of socioeconomic mobility; a level that is considered low by international standards. The US's level of socioeconomic mobility has historically been low, with little to no progress over the last three to four decades. Before it embarked on its transition from planned to market economy, socioeconomic mobility was relatively high in China. However, as it underwent a period of rapid economic growth, China's socioeconomic mobility declined significantly. The paper concludes that the world's two major economic powers have converged to a low level of socioeconomic mobility where talent from disadvantaged backgrounds is excluded from opportunities, plausibly implying unrealized human potential and misallocation of resources on a large scale.
Keywords: D3; D6; I24; J62; 330; intergenerational mobility; inequality; equality of opportunity; education; income; China; United States